Genetic variation of Limnophora marginata Stein, 1904 (Diptera: Muscidae), associated with an altitudinal gradient in Pedro Moncayo Canton, Pichincha, Ecuador (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Aguilar KEV, Vivas AYS, Acosta-López C. 2023. Genetic variation of Limnophora marginata Stein, 1904 (Diptera: Muscidae), associated with an altitudinal gradient in Pedro Moncayo Canton, Pichincha, Ecuador. Biodiversitas 24: 269-275. Analyzing heterogeneity in insect populations is relevant to understanding its biology. Thus, we analyzed the genetic variability of two populations of “hunter-flies”, Limnophora marginata Stein, 1904 associated with an altitudinal gradient in the Tocachi and Jerusalem localities, in the Pedro Moncayo Canton, Ecuador, using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) of the mitochondrial Cytochrome oxidase I gene. Thirty alleles were detected from analysis with five restriction enzymes; the percentage of polymorphic loci was higher in Tocachi (96.67%) than in Jerusalem (80%). Haplotypes were generated with the corresponding alleles, resulting in a different haplotype for each analyzed individual. Several estimators were used to characterize the population structure. The Analysis of Molecular Variance (AMOVA) evidenced the existence of higher intra-population variability (94%) than inter-population (6%), showing similar information to that found through haplotype analysis. The Fst fixation index indicated that there is no genetic difference between populations (0.056, P
Keywords: COI gene, genetic variability, hunter—flies, molecular markers, PCR-RFLP